CHOICE OF CREDIT FACILITIES: A STIMULANT FOR FINANCIAL PERFORMANCE OF SMES IN NIGERIA - Ajajyi, Modupe Olayinka (Archives of Business Research, 2019)
The study examined the effects of choice of credit facilities on the financial performance of SMEs in Nigeria while the specific objectives are to establish the influence of interest rate on loan and service on performance of registered SMEs in Ekiti State; investigate the influence of trade credits on performance of registered SMEs in Ekiti and examine the effect of asset financing on performance of registered SMEs in Ekiti State. The population of the study comprised 1704 SMEs operators from 16 local government areas in Ekiti State Nigeria. The stratified sampling technique was used to select the sample size from the captive population. The total sample size is 324 SMEs. This is the minimum to go to field with. 10% of 324were added to the sample size, summing up to give 356 because of non-response rate. To achieve the set objectives and hypotheses, both descriptive and inferential statistics were employed. In the descriptive analysis, the use of percentages comes to bare; more importantly in the areas of frequency of respondents to their views on the questions of research instrument. In specific terms, to achieve the objectives ANCOVA analysis were adopted. The results revealed that interest loan and performance between the groups revealed that a statistically significant main effect [f(16.961, 14.244) = 9.207, p < .05], loan and performance between the groups revealed that a statistically significant main effect [f(8, 1) = 2.952, p < .05] and bonds and performance between the groups revealed that a statistically significant main effect [f(16, 1) = 4.998, p < .05]. The study concluded that there is improvement in businesses of the customers who use Micro-Credit loans, loan repayment is a smooth process and Cash and deposit account at depository institutions, the short term loan, there is no special terms granted, no, special terms occasionally granted and term frequently granted, capital provided by the owners or shareholders of the enterprise are credit worthiness that is your track record of repaying past debts.